26.4k views
4 votes
-5x=y+2
2(2x-1)=3-3y
What is the solution (x, y) to the system of equations above?

1 Answer

3 votes

(-1, 3)

Explanation:

1st step: put x and y together

-5x = y + 2

5x + y = -2

2 × (2x - 1) = 3 - 3y

4x - 2 = 3 - 3y

4x + 3y = 5

2nd step: make the one similar (x or y)

5x + y = -2 ×(+3)

4x + 3y = 5 ×( -1)

15x + 3y = -6

-4x - 3y = -5

3rd step: collection process

15x + 3y = -6

-4x - 3y = -5

11x = -11

x = -1

The last step: write -1 instead of x in any equation

-5x = y + 2

-5×(-1) = y + 2

5 = y + 2

y = 3

The answer is ( -1, 3)

My English is not good, I hope this will help you..

User Sam Denty
by
4.5k points